STRATEGI MENGATASI PROBLEM BELAJAR PADA SISWA YANG BERPRESTASI RENDAH - Endang Palupi (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2019)
Education is something very important in human life. With human education it is able to explore and develop the potential given by God in everyone. Many ways are taken by people to get education, one of them is formal education. In the school environment students are a barometer of success in the education system. Therefore improving the quality of students is very important in the teaching and learning process in schools. The main cause of low student achievement is the weak student learning strategy. Most low achieving students do not know how they study well according to their abilities. This study aims that students who have low learning achievement can improve their learning achievement. The subjects of the study were class VI SDN 4 Banyuasin II students and involved teachers, principals and parents. The method used to improve student learning achievement is group discussion, memorizing, reading and taking notes. In this discussion there is also responsibility and self-esteem. The method in this study is a type of qualitative research, because it is done using information obtained through instruments of data collection, interviews, and observation.